In Vitro Morpho-Anatomical and Regeneration Features of Cultivars of Actinidia kolomikta (Maxim.) Maxim - Irina Leonidovna Krakhmaleva; Olga Ivanovna Molkanova; Natalia Dmitrievna Orlova; Olga Vasilevna Koroleva; Irina Vjacheslavovna Mitrofanova (Horticulturae)
Actinidia kolomikta (Maxim) Maxim. is a winter-hardy species of the genus Actinidia Lindl., whose fruits are valued for their high content of vitamin C and other bioactive compounds. The use of biotechnological propagation methods significantly accelerates the production of quality planting materials for this crop. This study revealed the regeneration features of promising A. kolomikta cultivars. The main morphometric parameters of explants were determined in regard to the effect of different iron chelates (FeEDTA and FeEDDHA) and cytokinins (6-benzylaminopurine, meta-Topolin, and 2-izopentyladenine) in the Quoirin and Lepoivre medium. FeEDTA-supplemented media were optimal for explant culture. Meta-Topolin was found to promote the formation of adventitious microshoots at the base of explants and bud activation, which increased the multiplication rate by 1.5 and 1.7 times compared to the media with 6-benzylaminopurine and 2-izopentyladenine. The morpho-anatomical studies revealed the structural organization of assimilation tissues and the stomatal apparatus of A. kolomikta under different culture conditions (field, in vitro, and ex vitro). The stomata in vitro were round and had a larger area, lower thickness, and a lower layer number of mesophyll compared to field conditions. The transfer from in vitro to ex vitro caused gradual normalization of the leaf structure: a decrease in the stomatal number and area, changes in shape (from round to elliptical), and an increase in the mesophyll thickness.